Realization of cognitive models of situations through phraseological units in English-language articles on culture - A. A. Asabina (Вестник Самарского университета: История, педагогика, филология, 2023)
Currently, in the media discourse, the authors of articles actively realize their pragmatic intentions through the pragmatic potential of phraseological units. The relevance of the study can be proved due to the fact that at the moment there is no information about the components of cognitive models of situations which can be most effectively used by the authors of articles to realize their pragmatic intentions through the pragmatic potential of phraseological units in articles of certain thematic groups. The purpose of the article is to determine the components of cognitive models of situations that are actualized and brought to the fore through the pragmatics of phraseological units in the texts of the English-language media discourse on the topic «culture», the reasons for the actualization of these components of cognitive models of situations by phraseological units, as well as to establish what pragmatic goals of the authors this is due. The study was conducted on the material of media texts – the texts of articles posted on the website of The Guardian newspaper. The research used methods of discourse analysis, semiotic analysis, observation and description techniques. As a result of the analysis of the articles on the topic «culture», it was identified that in the most of the examples the components «situation» and «circumstances» of cognitive models were brought to the fore through the pragmatics of phraseological units, also there was determined the cause of this phenomenon.